Programming Ethics in Self-Driving Cars: Ethical Dilemma - Najam Ul Hassan (SEISENSE Journal of Management, 2018)
Self-driving cars promise to revolutionize the automotive industry. Besides being productive and fuel-efficient, they would be significantly safer than the human-operated cars. However, in the rare case when they do get into an accident, they can calculate and opt for the reactive measure to take based on their programming. The manufacturer, it seems, must decide the ethics that self-driving cars should follow in such scenarios. In circumstances where they must choose between the lives of the passengers and the pedestrians, some researchers have argued that the best solution is to choose for the safety of the passengers over the pedestrians. Such a strategy, they argue will make sense as cars will have better control over the passenger and, therefore, will help in faster adoption of self-driving cars. However, this line of thinking seems simplistic at best. The author suggests areexamination of the ethical issues while taking into account the social and technological aspects as well.